The Challenges of Informed Consent in High-Stakes, Randomized Oncology Trials: A Systematic Review. Issue 1 (March 2019) - Nathe, Julia M.; Krakow, Elizabeth F.
Importance. Oncology trials often entail high-stakes interventions where potential for morbidity and fatal side effects, and for life-prolongation or cure, intensify bioethical issues surrounding informed consent. These challenges are compounded in multistage randomized trials, which are prevalent in oncology.Objective. We sought to elucidate the major barriers to informed consent in high-stakes oncology trials in general and the best consent practices for multistage randomized trials.Evidence Review. We queried PubMed for original studies published from January 1, 1990, to April 5, 2018, that focused on readability, quality, complexity or length of consent documents, motivation and sickness level of participants, or interventions and enhancements that influence informed consent for high-stakes oncologic interventions. Exclusion criteria included articles focused on populations outside industrialized countries, minors or other vulnerable populations, physician preferences, cancer screening and prevention, or recruitment strategies. Additional articles were identified through comprehensive bibliographic review.Findings. Twenty-seven articles were retained; 19 enrolled participants and 8 examined samples of consent documents. Methodologic quality was variable. This body of literature identified certain challenges that can be readily remedied. For example, the average length of the consent forms has increased 10-fold from 1987 to 2010, and patient understanding was shown to be inversely proportional to page count; shortening forms, or providing a concise summary as mandated by the revised Common Rule, might help. However, barriers to understanding that stem from deeply ingrained and flawed sociocultural perceptions of medical research seem more difficult to surmount. Although no studies specifically addressed problems posed by multiple sequential randomizations (such as change in risk-benefit ratio due to time-varying treatment responses or organ toxicities), the findings are likely applicable and especially relevant in that context. Concrete suggestions for improvement are proposed.